Genres and Provenance in the Comedy of W.S. Gilbert : Pipes and Tabors - Moore, Richard, 1945- (New York : Routledge, 2019)
In The Progress of Fun W.S. Gilbert was considered, not as a 'classic Victorian', but as part of an on-going comedic continuum stretching from Aristophanes to Joe Orton and beyond. Pipes and Tabors continues the story, covering the comedic experience differently by reference to genres. Here - treated in relation to a line of significant others - we discover how Gilbert responded to areas such as the Pastoral, the Irish drama, nautical scenarios, melodrama, sensation-theatre, the nonsensemode, pantomime spectaculars, fairy plays, and classical farce. Also included is a wider look at his relation to various European musical forms and (for instance) to the English line of wit and the Elizabethan pamphleteers. To consider a writer not so much by a study of individual works as by threads of linking generic modes tells us a great deal about cultural interconnections and the richly textured nature of theatrical experience. Pipes and Tabors offers a tapestry of overlapping genres and treatments, showing not just the design of the finished products but the shreds and patches which form the underside of the weave. According to Dorothy L. Sayers, life itself offers us the apparent loose ends of a design which will only be revealed from the front after death. In terms of Gilbertian comedy, we are privileged to be able to track both the effort of the weave and the skill of the finished product. On the way we will also discover some new links and sub-text implications about other 19th century denigrated groups which were buried from sight for too long.
Introduction : Intention and Parameters. Part One : Background and Developments Part Two : Genres and Their Treatment : a) Masque, Dumb-Show and the Pastoral b) Irish Drama: Examples from Boucicault and Elsewhere c) Opera, Tragedy and Politics : The Burlesque Response d) Nautical Burlesque c) Burlesque Melodrama and Gothic Parody d) Burlesque Sensation e) Nonsense and Surrealism. f) Pantomime g) Genres of the Supernatural : Fairies, Diabolism and the Realm of Magic h) Farce as a genre and expression of the Comic Spirit. Part Three : Other genres and Concluding Observations.
OCLC-licensed vendor bibliographic record.
Keywords: LITERARY CRITICISM / General; Gilbert, W. S. -- 1836-1911 -- Criticism and interpretation; English drama (Comedy) -- History and criticism